2022
DOI: 10.1055/s-0042-1743232
|View full text |Cite
|
Sign up to set email alerts
|

Early Superior Clinical Outcomes in Robotic-Assisted TKA Compared to Conventional TKA in the Same Patient: A Comparative Analysis

Abstract: Robotic-assisted total knee arthroplasty (RA-TKA) has demonstrated improved alignment and outcome scores when compared with manual total knee arthroplasty (M-TKA); however, few studies compare differences in the same patient. This study is a retrospective review that assesses clinical outcomes of 36 patients who underwent a primary RA-TKA and had undergone a prior contralateral M-TKA. All surgeries were performed by a single surgeon at the same institution. Patients were assessed for differences in hospital le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This may be attributable to better preservation of the periarticular soft tissue envelope in RO TKA enabling patients with higher functional demands to return to their pre‐disease level of activity with less “awareness” of the affected joint [7, 12, 22]. Similar trends of improved outcomes using robotic surgery compared with conventional manual surgery have also been shown in studies reporting on other robotic platforms for both TKA and unicompartmental knee arthroplasty [3, 9, 14]. Choi et al retrospectively reviewed outcomes in 120 patients and reported that the RO TKA improved patient satisfaction scores and patient‐reported outcome measures compared with CO TKA at two‐year follow‐up [11].…”
Section: Discussionmentioning
confidence: 75%
“…This may be attributable to better preservation of the periarticular soft tissue envelope in RO TKA enabling patients with higher functional demands to return to their pre‐disease level of activity with less “awareness” of the affected joint [7, 12, 22]. Similar trends of improved outcomes using robotic surgery compared with conventional manual surgery have also been shown in studies reporting on other robotic platforms for both TKA and unicompartmental knee arthroplasty [3, 9, 14]. Choi et al retrospectively reviewed outcomes in 120 patients and reported that the RO TKA improved patient satisfaction scores and patient‐reported outcome measures compared with CO TKA at two‐year follow‐up [11].…”
Section: Discussionmentioning
confidence: 75%
“…Ali et al also found shorter LOS and earlier recovery in patients undergoing CI TKA on one knee and RAS TKA on the other using MAKO RAS system. 27…”
Section: Discussionmentioning
confidence: 99%
“…The exact alignment strategy was not described in that study, but since MAKO was used, one can assume aMA was used. Ali et al also found shorter LOS and earlier recovery in patients undergoing CI TKA on one knee and RAS TKA on the other using MAKO RAS-system 27 .…”
Section: Accepted Manuscriptmentioning
confidence: 94%
“… 14 Recent literature suggests that robotic-assisted TKA (RATKA) leads to superior early postoperative outcomes when compared with patients operated on with conventional methods. 15 , 16 It is well known that arthrofibrosis is a potential complication after TKA. Arthrofibrosis is estimated to be responsible for 28% of 90-day hospital readmissions and 10% of revision surgeries within the first 5 years postoperatively.…”
mentioning
confidence: 99%